"دور التسويق الإبتكاري في ترقية النشاط السياحي -دراسة حالة - المسلسلات التلفزيونية كأداة تسويقية مبتكرة " - سميرة, التجاني; سمية, كحلة (University of eloued جامعة الوادي, 2020)
"التسويق الإبتكاري يعد إحدى الأساليب الإستراتيجية الهامة والضرورية التي تساهم في بناء وترقية النشاط السياحي و يعتبر أيضا خيارا إستراتيجيا يضمن له مواجهة الإضطربات المختلفة، و عليه فإن خلق مزيج تسويقي مبتكر متكامل و القيام بأنشطة تسويقية مبتكرة تساهم في زيادة تطوير و ترقية النشاط السياحي . وعليه تهدف هذه الدراسة إلى التعرف على دور التسويق الابتكاري في النشاط السياحي ، من خلال تحديد الدور الذي يلعبه التسويق الابتكاري في المسلسلات التلفزيونية كنموذج يؤدي إلى زيادة وتنشيط قطاع السياحة وطنيا ودوليا ، ولهذا الغرض ثم تقسيم الدراسة إلى شقين ، شق يتعلق بالجانب النظري وفيه تعرضنا للتسويق الابتكاري ومفاهيمه ومتغيراته بصفة عامة ، أما الشق الثاني فيتعلق بالجانب التطبيقي وتطرقنا فيه إلى دراسة أثر التسويق الابتكاري على نشاط السياحة من خلال المسلسلات التلفزيونية كنموذج، وتطبيق التسويق الابتكاري على مكونات المزيج التسويقي السياحي, و لقد دعمت هذه الدراسة بإجراء دراسة تطبيقية على المسلسلات التلفزيونية باستخدام استبيان إلكتروني موجه لمتابعة المسلسلات مع تطبيق مزيج التسويق الإبتكاري السياحي بعناصره (الإبتكار في المنتج، الإبتكار في الأسعار، الإبتكار في الترويج، الإبتكار في التوزيع، في الأفراد، في البيئة المادية و في العمليات) وإظهار دوره الكبير والفعال ا في تحقيق ترقية النشاط السياحي من خلال زيادة جودة المسلسلات و زيادة تميزها للاستجابة للسياحة. "" Innovative marketing is one of the important and necessary strategic methods that contribute to building and promoting tourism activity and is also considered a strategic option that guarantees him to face different disturbances , and therefore creating an innovative integrated marketing mix and carrying out innovative marketing activities that contribute to the further development and promotion of tourism activity. Accordingly, this study aims to identify the role of innovative marketing in the tourism activity, by defining the role that innovative marketing plays in TV series as a model that leads to increasing and revitalizing the tourism sector nationally and internationally. For this purpose, then the study is divided into two parts, an aspect related to the theoretical side and in which we are exposed to marketing The innovative and its concepts and variables in general, while the second part relates to the applied side and we touched upon it to study the impact of innovative marketing on tourism activity through TV series as a model, and the application of innovative marketing to the components of the tourism marketing mix, and this study supported the implementation of an applied study on TV series using a questionnaire Electronic directed to follow the series with the application of the mix of tourism innovative marketing with its elements (innovation in the product, innovation in prices, innovation in promotion, innovation in distribution, in individuals, in the physical environment and in operations) and show its great and effective role in achieving the promotion of tourism activity through Increase the quality of the series and increase their distinctiveness in response to tourism "
مذكرة ماستر تسويق فندقي وسياحي
Keywords: الإبتكار، التسويق الإبتكاري، التسويق السياحي، المزيج التسويقي السياحي.; innovation, innovative marketing, tourism marketing, tourism marketing mix